IDENTIFIKASI JENIS-JENIS POHON PENYUSUN VEGETASI GAMBUT TAMAN NASIONAL DANAU SENTARUM KABUPATEN KAPUAS HULU - Randi, Agusti; Manurung, Togar Fernando; Siahaan, Sarma (JURNAL HUTAN LESTARI, 2014)
Borneo has a diversity of flora is very rich, this island is a center of plants diversity. Approximately 15.000 species of flowering plants found in this island and there are more than 3000 species of which are trees. The data of plant species diversity in Kalimantan forests (Indonesia) is still lacks, in particular the data about tree species on peat swamp forests.The research was conducted on the peat swamp forest in Danau Sentarum National Park, Kapuas Hulu regency, West Kalimantan. The purpose of this study is to know the trees species as the compiler of peat swamp vegetation in Danau Sentarum National Park with do identification. The method used in this research is the exploration and collection of flora that is done by way of cruising on the line transect, with exploring every corner of the research areas that can represent the type of ecosystem or vegetation types in the areas studied. Base on research, peat swamp forest in Danau Sentarum National Park has a diversity of tree species are quite high with the discovery of 107 trees species are classified into 48 family. From 48 family were found, Dipterocarpaceae is found with the highest number with 12 species. Diversity of flora in the peat forest is not too rich when compared to the diversity of flora in the mixed Dipterocarp forest, but most of the flora species grown on peat swamp forests is specific species because it is relatively rare found in other forest types. Keywords : Idenfication, Tree Species, Peat Swamp, Danau Sentarum